Malignant Pancreatic Tumors in Children and Young Adults: Evaluation of 228 Patients Identified through the Surveillance, Epidemiology, and End Result (SEER) Database - Brecht, I. B.; Schneider, D. T.; Klöppel, G.; von Schweinitz, D.; Barthlen, W.; Hamre, M. R. (Klinische Pädiatrie, 2011)
Malignant pancreatic tumors are rare in young patients, few epidemiologic data are available. We reviewed prognostic factors and outcome of 228 patients <30 years with malignant pancreatic tumors identified through the U.S. National Cancer Institute’s SEER (Surveillance, Epidemiology, and End Results) Public-use Database from 1973 to 2004.Cases were grouped using the ICD-O-3. 5-year overall survival (OAS) was assessed by gender, ethnicity, SEER stage, and 5-year age intervals using univariate and Cox regression analysis.228 patients with malignant pancreatic tumors were identified, resulting in an incidence of 0.46/million (100 carcinomas, 85 endocrine tumors, 8 solid pseudopapillary neoplasms (SPN), 11 pancreatoblastomas) in the USA. OAS was worse in males than females (37% vs. 55%, p=0.005). OAS according to stage was 87%, 68%, 21% for local (n=54), regional (n=42), distant metastatic disease (n=108), respectively. OAS of patients with carcinoma was 33%, endocrine tumors 58%, SPNs 88%, pancreatoblastomas 66%. Cox regression revealed stage (p=< 0.001), histology (p=< 0.001), age group (p=0.05) to be independent prognostic factors.Malignant pancreatic tumors are extremely rare in children and young adults. Entities change over the age groups towards more carcinomas with worse outcome in older patients. Tumor stage, histology and age group are important predictors for outcome. International collaboration is needed to learn more about pediatric pancreatic tumors.
Keywords: primary pancreatic tumors; pediatric malignant tumors; epidemiology; SEER database; rare tumors; young adults